Effect of Adding Different Ratios of Oat (Avena sativa L.) Cracks on the Silage Quality of Fodder Pea (Pisum arvense L.) - TENİKECİER, Hazım Serkan and ATEŞ, Ertan (ISPEC Tarım Bilimleri Dergisi, 2024)
Silage is an optimal method for preserving high-quality forage and forage legumes are vital feed resources for ruminants and can be utilized in various forms, including hay, silage, and grazing. The fodder peas is a versatile crop, utilized for grain production, herbage, hay, pasture, green manure, and silage, either as a monoculture or in combination with cereals. Feeds such as fodder peas, characterized by high levels of crude protein, mineral content, and buffering capacity, but low levels of water-soluble carbohydrates, require the addition of specific additives to enhance silage fermentation. The research was conducted to determine the effect of the cracked oat grains on fodder peas silage quality. Fresh fodder peas was harvested at full-bloom stage and ensiled with 3 %, 6 % 9 % and 12 % added cracked oat grains in plastic bags for 45 days. The crude protein (%), crude ash (%), ADF (%), NDF (%), P (%), K (%), Ca (%), Mg (%), digestible dry matter (DDM) (%), dry matter intake (DMI) (%), total digestible nutrients (TDN), net energy-lactation (NEl), net energy-maintenance (NEm), net energy-gain (NEg), fleig score, and relative feed value (RFV) were determined. The dry matter of ensiled fodder peas and cracked oat grain added fodder peas silage varied between 38.30-39.54%. The pH values were between 4.15-4.50 in silage of fodder peas and cracked oat grain added fodder peas silages. Fleig score values were varied between 101.47-118.21. According to the Fleig scores, adding 12% cracked oat grains to fodder peas during siloing may be recommended to obtain silage.